Fatigue life evaluation of adhesive joints in a real structural component. (December 2021) - Antelo, J.; Akhavan-Safar, A.; Carbas, R.J.C.; Marques, E.A.S.; Goyal, R.; da Silva, L.F.M.
Abstract: The aim of this work is to study how well fatigue life predictions, based on Arcan tests results, apply to real joint with a complex geometry, used as a structural component in industrial vehicles. Using a stress-life approach, a master stress-life curve for fatigue was constructed. By utilizing the master curve, fatigue life predictions were made for the joints and compared with the welded assembly. Experimental fatigue tests were performed to verify the predictions. The results agreed with the fatigue life predictions. It was concluded that adhesive bonding is a suitable alternative to welding in terms of longevity. Highlights: Fatigue life of an industrial real joint were analyzed experimentally and numerically. Two different joining techniques including adhesive bonding and welding were used. A new fatigue life prediction method based on the S-N approach was developed. Results showed superior performance for the bonded structure compared to welding in high cycle fatigue regimes. The predicted life was in good agreement with the experimental results.